The Antibacterial Effect of Additional Photodynamic Therapy in Failed Endodontically Treated Teeth: A Pilot Study - Asnaashari, Mohammad; Homayuni, Hamed; Paymanpour, Payam (Journal of Lasers in Medical Sciences, 2016)
Introduction: Root canal therapy as a routine dental procedure has resulted in retention of millions of teeth that would otherwise be lost. Unfortunately, successful outcomes are not always achievable within initial endodontic treatments, and that necessitates further treatment. Nonsurgical retreatment is the first choice in most clinical situations. The aim of this clinical pilot study was to assess the effect of additional photodynamic therapy (PDT) on intraradicular bacterial load following retreatment of failed previously root treated teeth. Methods: Thirty single-rooted/canalled endodontically treated matured teeth (in 27 healthy patients) accompanied by apical periodontitis (AP) were selected for this study. Standard protocol was followed for nonsurgical retreatment of each tooth. Microbiological samples were taken after establishment of apical patency, finished cleaning/shaping procedure, and PDT (665 nm, 1 W, 240 seconds). All samples were cultured for 72 hours and colony-forming unit (CFU) was counted. McNemar test was used for statistical analysis of the data. The level of significance was set at 0.001. Results: Routine cleaning and shaping resulted in twenty four negative (80%) out of 30 cultures. Four additional negative results were obtained after additional PDT (93.3%). The addition of PDT to routine procedures significantly enhanced the number of bacteria-free samples (P < 0.001). Conclusion: Regarding elimination of intraradicular microbiota, additional PDT may increase the effectiveness of conventional chemomechanical preparation in previously root filled teeth accompanied by AP. Well controlled randomized clinical trials should be planned for future.